Selected writings of Girolamo Savonarola : religion and politics, 1490-1498 - Savonarola, Girolamo, 1452-1498 (Italian literature and thought series., 2006)
This is a comprehensive collection of Savonarola's works and includes translations of his sermons and treatises on pastoral ministry, prophesy, politics and moral reform, as well as correspondence with Alexander VI that led to Savonarola's silencing and excommunication.